Predicting Preeclampsia in Early Pregnancy - Najmutdinova D. K.; Iriskulov B. U.; Kamilova I. A.; Hamdamov I. F. (Researchparks Publishing, 2022)
Preeclampsia and its complications, despite the rapid development of medical sciences, remain one of the most urgent problems even in developed countries. Although maternal mortality from hemorrhage and sepsis in obstetrics has been decreasing since the middle of the 20th century, the death rate from hypertensive conditions, especially preeclampsia, remains high.